Distinguishing the Roles of the Dorsomedial Prefrontal Cortex and Right Temporoparietal Junction in Altruism in Situations of Inequality: A Transcranial Direct Current Stimulation Study - Zhang, Hanqi; Dong, Zhiqiang; Cai, Shenggang; Zhao, Jun (Frontiers in Human Neuroscience, 2022)
The right temporoparietal junction (rTPJ) and dorsomedial prefrontal cortex (dmPFC), which are involved in social cognition, have been proposed to play key roles in guiding human altruistic behavior. However, no study has provided empirical evidence that the rTPJ and dmPFC play distinct roles in altruism under situations of inequality. A total of 89 healthy young adults were randomly assigned to receive anodal or sham transcranial direct current stimulation (tDCS) to either the dmPFC or rTPJ, and they participated in a modified dictator game. The stimulation of the dmPFC increased the level of altruistic behavior, while the stimulation of the rTPJ did not. Furthermore, we determined that the increase in altruism induced by tDCS of the dmPFC could be modulated by perspective taking. These results demonstrate that the dmPFC and rTPJ play distinct roles in the enhancement of altruism in situations of inequality; this finding is consistent with theories proposing that the dmPFC has evolved mechanisms dedicated to perspective taking.